(untitled) - Mauk, David (London,New York, 2009)
This hugely successful text provides students of American studies with the perfect background and introductory information on contemporary American life. Thoroughly revised, this fifth edition covers all the central dimensions of American society from geography and the environment, government and politics, to religion, education, media and the arts.
Keywords: Hoa Kỳ,Văn minh,Dạy và học